Rafraîchir les observatoires par le son - Cécile Regnault; Patrick Romieu (Projets de Paysage)
From the most notable disruptive innovations dating from the First World War to more seemingly mundane experiments such as the transistor, this article offers a theoretical and methodological look at sound observatories. It does not pretend to present an exhaustive list of the state of the art in nascent investigative methods and practices for describing the subtle and complex inflections of the everyday sounds which surround us and of which any connection with current landscape theories appears as tenuous and arguable. Such a theoretical approach combines anthropology with urban planning and architecture and its methodology takes inspiration from action research. The critical argument is essentially based on two unpublished bodies of work conducted at two experimental sites and reviews the results of close to 20 years of concurrent experiments conducted by two French associations, Aricène and aCousson4. Without disowning the preventive contributions of the Noise Observatories, the systems described here are the result of the intention to present sound as a major societal phenomenon of the 21st century and represent creative resources which may be used in any landscape project. Their final objective is to take acoustic and aesthetic values jointly into consideration in order to identify common sound cultures. It is difficult to share sound environments outside the immersive experience of everyday life. The perception, classification, and ranking of the qualities of these sound environments are born from collective historical experiences and instituted systems of taste just as much as they are born from individual aesthetic experiences. These coextensive heterogeneities of sound media require theoretical and methodological rigour on the part of collective organisations in charge of their mediations.